2021
DOI: 10.1002/jts5.87
|View full text |Cite
|
Sign up to set email alerts
|

Who pays it forward the most? Examining organizational citizenship behavior in the workplace

Abstract: This work examines individual employee's tendencies to engage in social exchange and organizational citizenship behavior, as a result of their commitment to the organization. It is desirable for organizations to have employees who go above and beyond their prescribed work duties, leading to a number of positive outcomes, such as increased work team effectiveness, increased quality, and quantity of work and elevated overall organizational performance (Podsakoff & MacKenzie, 1997;Podsakoff et al., 2000). This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 117 publications
0
4
0
1
Order By: Relevance
“…This study's hypotheses draw from tenets of the Social Exchange Theory (SET) and positive psychology to offer theoretical explanation for the link between agile-Omoluabi leadership, technology transfer, government willingness to change, engagement, workplace happiness; and citizen behaviour. As Blau articulated it in 1964, SET provides a framework for understanding the dynamics at play in human relationships (Andriyanti & Supartha, 2021;Eriksson & Ferreira, 2021). The SET assumes three mechanisms at work: (1) the first treatment of a target by an actor, (2) the target's responses to that action, and (3) the development of a relationship between the two parties.…”
Section: 1theory and Hypotheses Developmentmentioning
confidence: 99%
“…This study's hypotheses draw from tenets of the Social Exchange Theory (SET) and positive psychology to offer theoretical explanation for the link between agile-Omoluabi leadership, technology transfer, government willingness to change, engagement, workplace happiness; and citizen behaviour. As Blau articulated it in 1964, SET provides a framework for understanding the dynamics at play in human relationships (Andriyanti & Supartha, 2021;Eriksson & Ferreira, 2021). The SET assumes three mechanisms at work: (1) the first treatment of a target by an actor, (2) the target's responses to that action, and (3) the development of a relationship between the two parties.…”
Section: 1theory and Hypotheses Developmentmentioning
confidence: 99%
“…Upstream and downstream reciprocity are commonly observed behaviors in experimental settings and field research [23][24][25][26][27][28][29][30]. Notably, different types of reciprocal mechanisms can be applied in tandem to promote cooperation [14].…”
Section: Introductionmentioning
confidence: 99%
“…This approach can be effective in remote settings, where each team member's input is valued and encouraged [12]. Organizational commitment needs to be addressed in contact-based and remote workplaces, and organizations need to focus on improving their leadership, communication, and recognition practices and providing clear expectations, feedback, and recognition to remote workers to increase their commitment [13]. Grego-Planer [14] revealed that OCB strongly correlates with work attitudes, task variables, and leadership behavior.…”
Section: Introductionmentioning
confidence: 99%